Implementation of Engineering Design Process in the K-12 Science Classrooms: Trends and Issues - Arik, Merve; Topcu, Mustafa Sami (SPRINGER, 2022)
The purposes of this research are to analyse studies which include Engineering Design Process by using meta-synthesis method and to present the type of tendency and differences of the processes used in the current literature. With this purpose, 46 research articles were selected and analysed. Qualitative data were collected under three categories based on the literature and the selected 46 articles. The results demonstrate that researchers mostly use open-ended questions and problem scenarios while presenting a design brief and use different teaching methods-mostly brainstorms, laboratory activities, and writing activities-while utilizing an engineering design process. And also while creating design artefacts, researchers use four different steps, namely, drawing, make, test, redesign. It is believed that this research will guide subsequent researchers and science teachers in planning and implementing engineering design process in K-12 classrooms.
Keywords: Engineering education in K-12; Engineering design process; Meta-synthesis study; Science education; SCHOOL; ENGAGE; Education & Educational Research